An Analytical Model of an Internal Political Crisis - Simeonova, Elena (Research Papers, 2008)
The study features an analytical model of an internal political crisis studied with a view to enable a “measurement” of the stability of a political system in the period of a transition from authoritarianism to democracy by means of an analysis of political crises emerging within the system. It is aggregate in nature because it is composed of three basic components – temporal, formal and theoretical. These components interpret the interrelationships of an internal political crisis – different viewpoints of political stability which enables analytical perspectives of the study.